2019
DOI: 10.1111/apt.15231
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the growing incidence and prevalence of eosinophilic oesophagitis in children and adults in population‐based studies

Abstract: Background:The frequency of eosinophilic oesophagitis (EoE) occurrence is escalating. Current diagnostic criteria recently proposed for the disease, determine that previous estimates of incidence and prevalence are outdated.Aim: To gauge the current incidence and prevalence of EoE by performing a systematic review of population-based studies.Methods: Three electronic databases were searched from their inception dates to September 2018. A total of 2386 documents were screened; 29 studies reported on the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
185
4
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(233 citation statements)
references
References 48 publications
(119 reference statements)
10
185
4
11
Order By: Relevance
“…1 The calcineurin inhibitors (ciclosporin and tacrolimus) and purine antagonists (mycophenolate mofetil and mercaptopurine) have been enlisted as rescue drugs. [1][2][3] Rescue regimens have been empiric, untested in head-to-head clinical trials and ascribed outcomes that have been variably defined.…”
Section: Editorial: Tailoring Mycophenolate Mofetil Rescue Therapy Fomentioning
confidence: 99%
See 2 more Smart Citations
“…1 The calcineurin inhibitors (ciclosporin and tacrolimus) and purine antagonists (mycophenolate mofetil and mercaptopurine) have been enlisted as rescue drugs. [1][2][3] Rescue regimens have been empiric, untested in head-to-head clinical trials and ascribed outcomes that have been variably defined.…”
Section: Editorial: Tailoring Mycophenolate Mofetil Rescue Therapy Fomentioning
confidence: 99%
“…Mycophenolate mofetil (MMF) has emerged as the most actively reported rescue medication. 2,4 The retrospective, multicentre, observational study of Nicoll et al 5 provides much needed guidance in selecting those individuals who are likely to achieve an optimal outcome (as defined by the European and American liver societies 6,7 )…”
Section: Editorial: Tailoring Mycophenolate Mofetil Rescue Therapy Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Variation exists in the literature on the prevalence of pediatric EoE where it is reported, varying between 0.2 and 43 cases per 100 000 . A recent meta‐analysis of population‐based studies published pooled the prevalence of pediatric EoE across North America and Europe to estimate overall prevalence at 34.4/100 000 and overall incidence at 6.6/100 000 . An increasing trend over the past decade has been captured in several reports; a recent cohort study in Utah found 24 cases/100 000 .…”
Section: Introductionmentioning
confidence: 99%
“…12 A recent meta-analysis of population-based studies published pooled the prevalence of pediatric EoE across North America and Europe to estimate overall prevalence at 34.4/100 000 and overall incidence at 6.6/100 000. 13 An increasing trend over the past decade has been captured in several reports; a recent cohort study in Utah found 24 cases/100 000. 14 Together with this study from Utah, figures for the epidemiology of EoE in European children were simultaneously provided by Arias et al 15 where the incidence was reported as 10.6/ 100 000 in children.…”
Section: Introductionmentioning
confidence: 99%